Letters and poems by the late Mr. John Henderson : with anecdotes of his life / by John Ireland. - Henderson, John, 1747-1785. (Tufts University. Tisch Library., 2016)
1 online resource (xii, 333, [3] p.); With a half-title and final leaf of errata.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.; Indexed in: English Short Title Catalog,T68610